2012
DOI: 10.1002/pc.22289
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and DC electrical conductivity of the composite films containing polyaniline‐carboxymethyl cellulose

Abstract: New polymer composites containing polyaniline‐carboxymethyl cellulose (PANI‐CMC) were prepared via the polymerization of aniline hydrochloride using different concentration (wt%) of sodium CMC using ammonium persulfate as an oxidant. The thermal stability and embedded crystallinity of the composites were investigated using thermogravimetric and X‐ray diffraction analysis method, respectively. The electrical properties of the composites were examined using temperature‐dependent DC conductivity within 300–500 K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Electrical conductance of the polymer composite is directly proportional to the electron mobility in the network. Basavaraja et al . have studied the effect of NaCMC on polyaniline polymer in terms of electrical conductivity and reported a significant increase in conductivity upon addition of NaCMC.…”
Section: Resultsmentioning
confidence: 99%
“…Electrical conductance of the polymer composite is directly proportional to the electron mobility in the network. Basavaraja et al . have studied the effect of NaCMC on polyaniline polymer in terms of electrical conductivity and reported a significant increase in conductivity upon addition of NaCMC.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the large molecular chain structure of anionic polyelectrolyte makes it more difficult to be removed from the conducting polymers than the small molecule acid, exhibiting a better stability once being doped in conducting polymers (Nguyen and de Vos 2004). In recent years, several works have demonstrated that using sodium alginate (SA) (Li et al 2011;Sahoo et al 2012), carboxymethylcellulose sodium (CMC) (Basavaraja et al 2012;Chou et al 2011;Peng et al 2012), poly(sodium-4-styrenesulfonate) (PSSNa) , and phosphorylated polyvinyl alcohol (PPVA) (Yang et al 2014) in the preparation process, various nanostructures of conducting polymers could be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The PEDOT, SC, and PESC composites did not show any kind of band beyond 2,000 cm −1 ; thus, to obtain clear and more detailed information, the FTIR spectra was shown in the range of 500–2,000 cm −1 . SC shows its characteristic absorption at 1,095 and 1,161 cm −1 , representing the stretching vibration of COH groups . The peak at the region 1,647 cm −1 might be originated by some amount of moisture in the sample.…”
Section: Resultsmentioning
confidence: 98%
“…The appearance of the absorption band at approximately 785 nm is assigned to the polaron and/or bipolaron band [33][34][35][36]. The SC shows an absorption band at around 300 nm, which is a characteristic band for cellulose [27,28]. Upon increasing the SC concentration, the nanocomposites show absorption bands related to both PEDOT and SC.…”
Section: Resultsmentioning
confidence: 99%